A comprehensive comparison of medication strategies for platinum-sensitive recurrent ovarian cancer: A Bayesian network meta-analysis - Liu, Yuanzhi; Huang, Yilan; Li, Jingyan; Wan, Shengli; Jiang, Nan; Yang, Jie; Chiampanichayakul, Sawitree; Tima, Singkome; Anuchapreeda, Songyot; Wu, Jianming (Frontiers in Pharmacology, 2022)
Background: The Platinum-based combination has been proven to have an outstanding effect on patients with platinum-sensitive recurrent ovarian cancer (PSROC), but the best scientific combination has not been established yet. The present study is aimed to seek the best treatment plan for PSROC. Methods: We did a systematic review and Bayesian network meta-analysis, during which lite before March 2022 were retrieved on PubMed, Embase, Web of Science, and Cochrane Central Registry of Controlled databases. We included randomized controlled clinical trials comparing chemotherapy combinations with other treatments for patients with PSROC. The important outcomes concerned were progression-free survival (PFS) (the primary outcome), overall survival (OS), objective response rate (ORR), adverse events (AEs), and AEs-related discontinuation. All outcomes were ranked according to the surface under the cumulative ranking curve. Results: 26 trials involving 10441 patients were retrieved in this study. For the initial treatment of PSROC, carboplatin plus pegylated liposomal doxorubicin (PLD) plus bevacizumab had the best PFS [hazard ratio (HR) 0.59, 95% credible interval (CI) 0.51–0.68]; Carboplatin plus paclitaxel plus bevacizumab resulted in the best OS (HR 1.22, 95% CI 1.09–1.35) and ORR [odds ratio (OR) 1.22, 95% CI 1.09–1.35]. For the maintenance therapy in PSROC, poly (ADP-ribose) polymerase inhibitors (PARPi) following platinum-based chemotherapy provided the best PFS (HR 0.64, 95% CI 0.61–0.68), the highest frequency of adverse events of grade three or higher (OR 0.18, 95% CI 0.07–0.44) but the treatment discontinuation was generally low. Subgroup analysis suggested that trabectedin plus PLD was comparable to single platinum in prolonging PFS in the platinum-free interval (6–12 months). Conclusion: Both platinum-based chemotherapy plus PARPi and platinum-based chemotherapy plus bevacizumab had higher survival benefits than other treatments in PSROC. Trabectedin plus PLD might be a potential alternative treatment strategy for the partially platinum-sensitive subpopulation with intolerance to platinum. Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/display_record.php?], identifier [CRD42022326573].